Furrow Lateral Wetting Potential For Optimizing Bed Width In Silty Clay†. (23rd December 2016) - Akbar, Ghani; Ahmad, Muhammad Munir; Khan, Matiullah; Asif, Muhammad
Abstract: Water application is generally assumed to be uniformly applied during furrow irrigation into the root zone of crops between the wetted furrows. However, non‐uniform distribution of applied water has been widely demonstrated along the field length, but there have been few studies focused on quantifying the lateral distribution of the wetting front from wetted furrows into the bed middle. Therefore, this study aimed to evaluate the lateral infiltration potential of wetted furrows spaced 132 cm apart for optimizing the bed width under silty clay. The results indicated a non‐uniform distribution of soil water shown by 33% less soil water movement into the middle of the bed compared with the furrow centre after 7 h of infiltration time, when field capacity was attained in the bed middle. Soil water movement simulation using the Hydrus 2D model was appropriate, which helped in identifying the optimized bed width for variable infiltration time under existing field conditions. The evaluation procedure and graphical presentation outcome may increase knowledge of the wetting time and lateral movement interaction that may support decision making in optimizing the bed width for improving water productivity by reducing yield loss due to a dry bed middle in the study area. Copyright © 2016 John Wiley & Sons, Ltd.